2015
DOI: 10.1186/s13613-015-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged prone positioning under VV-ECMO is safe and improves oxygenation and respiratory compliance

Abstract: BackgroundData are sparse regarding the effects of prolonged prone positioning (PP) during VV-ECMO. Previous studies, using short sessions (<12 h), failed to find any effects on respiratory system compliance. In the present analysis, the effects of prolonged PP sessions (24 h) were retrospectively studied with regard to safety data, oxygenation and respiratory system compliance.MethodsRetrospective review of 17 consecutive patients who required both VV-ECMO and prone positioning. PP under VV-ECMO was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 22 publications
3
85
2
1
Order By: Relevance
“…Notably, EIT-identified optimal PEEP before PP did not differ significantly between PCG+ and PCG− (P = 0.09). It was significantly reduced after PP in all patients, shifting from 14.8 (12)(13)(14)(15)(16)(17) to 11.7 (9-14) cmH 2 O for PCG+ , while PCG−, optimal PEEP declined from 12 (8-15.5) to 9 (6.5-11.5) cmH 2 O (Fig. 5).…”
Section: Eit-identified Optimal Peepmentioning
confidence: 90%
See 1 more Smart Citation
“…Notably, EIT-identified optimal PEEP before PP did not differ significantly between PCG+ and PCG− (P = 0.09). It was significantly reduced after PP in all patients, shifting from 14.8 (12)(13)(14)(15)(16)(17) to 11.7 (9-14) cmH 2 O for PCG+ , while PCG−, optimal PEEP declined from 12 (8-15.5) to 9 (6.5-11.5) cmH 2 O (Fig. 5).…”
Section: Eit-identified Optimal Peepmentioning
confidence: 90%
“…Although the use of PP combined with ECMO is still controversial [12], few studies have suggested that it could improve oxygenation and static compliance [13,14], thereby preventing subsequent VILI, when associated with "ultra-protective" ventilation. To date, PP physiological effects on regional ventilation and the optimal positive end-expiratory pressure (PEEP) level in this specific population with very low VT and altered static compliance are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In 17 subjects undergoing VV-ECMO who also failed at least one weaning attempt, prolonged prone positioning (24 hours) was performed [65]. Respiratory system compliance increased from 18 (12–36) to 32 (15–36) mL/cmH 2 O ( p < 0.0001), and the PaO 2 /FiO 2 ratio increased from 111 (84–128) to 173 (120–203) mmHg ( p < 0.0001).…”
Section: Prone Positioning Of Patients During Ecmomentioning
confidence: 99%
“…The other advantage of the DLB cannula is that it avoids additional femoral cannulation. This allows the use of prone positioning that is currently a common practice implemented in VV-ECMO patients to improve lung recruitment and oxygenation (42) and a patient's early mobilization, such as sitting up in bed and even ambulating, while on VV-ECMO support (43). Ambulatory ECMO programs have been developed in an attempt to provide rehabilitation, physical therapy and minimization of sedation prior to lung transplantation to improve both surgical and post-transplant outcomes.…”
Section: Double Lumen Single Bicaval Vv-ecmo Cannulationmentioning
confidence: 99%